2010
DOI: 10.1111/j.1365-2605.2009.00957.x
|View full text |Cite
|
Sign up to set email alerts
|

Semen quality, reproductive hormones and fertility of men operated for hypospadias

Abstract: The testicular function of men previously operated for hypospadias has been sparsely investigated. Therefore, we investigated semen quality and reproductive hormones of 92 men with isolated hypospadias (IH) and 20 with hypospadias and additional genital disorders (HAGD) and compared with similar results from young men from the general Danish population. All participants lived the Copenhagen area of Denmark. Additionally, fertility information on 1083 men registered as operated for hypospadias was retrieved fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 38 publications
(60 reference statements)
3
34
2
Order By: Relevance
“…In a recent study, Asklund et al [37] found that the semen quality of men with operated isolated hypospadias did not differ from controls, but that semen quality was reduced in men with hypospadias and additional genital disorders, predominately cryptorchidism. In 42% of these patients, a sperm density less than 20 million/mL was found.…”
Section: Fertility Aspectsmentioning
confidence: 95%
“…In a recent study, Asklund et al [37] found that the semen quality of men with operated isolated hypospadias did not differ from controls, but that semen quality was reduced in men with hypospadias and additional genital disorders, predominately cryptorchidism. In 42% of these patients, a sperm density less than 20 million/mL was found.…”
Section: Fertility Aspectsmentioning
confidence: 95%
“…Caucasian men are at particularly high risk of testicular cancer, which currently affects ∼1% of the Danish and Norwegian male populations 4. It has been proposed that most cases of TGCC, and some cases of hypospadias, cryptorchidism and decreased spermatogenesis (excluding those unrelated to development of the fetal testis) may be symptoms of a testicular dysgenesis syndrome (TDS) that originates from perturbations during fetal development 2 5…”
Section: Introductionmentioning
confidence: 99%
“…These findings are consistent with the recent study by Serrano et al [2013], which revealed the lack of geographic correlation in the prevalence of hypospadias and SF. Furthermore, Asklund et al [2010] have shown that semen quality remains unaffected in most patients with isolated hypospadias, whereas it was frequently compromised in patients with hypospadias and additional genital abnormalities. Subfertility of hypospadias patients is likely to be ascribed to some factors such as psychological aspects and sexual dysfunction rather than SF.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, although previous studies have shown that patients with hypospadias tend to have fewer children than the unaffected population [Asklund et al, 2010], the etiological relationship between SF and hypospadias has yet to be clarified. To date, only 2 studies examined the frequency of AZF-linked CNVs in patients with hypospadias.…”
Section: Y Chromosomal Cnvs and Hypospadiasmentioning
confidence: 99%